An axiological study on Islamic visual art in Malaysia from 1957 to 1999 / Wan Samiati Andriana W. Mohamad Daud - W. Mohamad Daud, Wan Samiati Andriana (Institute of Graduate Studies, UiTM, 2017)
The Islamic values were determined from Allah SWT through the Al-Quran and the guidance of the Prophet Muhammad SAW. The aims of this study were to determine the axiological aspect of the Contemporary Malaysian Islamic Visual Art, to explore the historical events and the development of the Malaysian Islamic Art from the year of 1957 to 1999, and to provide a comprehensive document on the history of the Contemporary Malaysian Islamic Visual Art based on history, tradition and culture of Islam. This research was conducted by using mixed methods of qualitative and quantitative research method. The quantitative research utilized questionnaire to solicit the data . The information gathered through data collection inclusive of three major issues, the concept, the national policies and the events or exhibitions gathered from various sources, including academic books, journal, proceedings as well as exhibition catalogues cum books of painting, retrospectives, biographies, competition booklets and website. The important events on Islamic art were also gathered through the articles presented at seminars and symposiums as well as newspaper cuttings and magazines. The study also analysed ninety five (95) pieces of artworks consist of artwork from painting, printmaking, sculpture and mix media such as collages, assemblages, digital print, fabric works and two-dimensional construction that were exhibited in Islamic Art exhibitions held in Malaysia from the years 1957 to 1999 and were selected from those created by the Muslim artists with the Islamic Art themes only…